The collocation in learning vocabulary: the Problems and pedagogical suggestions - Meylina Meylina (Jurnal Ilmiah Pendidikan Scholastic, 2018)
This was a descriptive qualitative research which was administered to 20 students of STMIK Jayanusa Padang. The data from the observation shown that the lack of collocation competence of the students noticeable when non-native speakers of English need productive language knowledge. they only experienced the limited number of lexical collocations they know or under the influence of their first language “create” unnatural and farfetched collocations. In order to solve this problem, this investigation aimed to expose the students' collocation problems in vocabulary teaching by using collocation tests and questionnaire. The data found were used to offer some pedagogical suggestions that can be applied in class as a starting point, especially to advanced students. Then it is hoped that students will have properly developed and balanced in learning collocations which will help them speak and write English in a more natural way.